The promotional language of the Halal food industry: some preliminary findings - Ariffin, Adlina; Wan Mohd Fadzlullah, Wan Nor Fasihah (2019)
The global halal food industry which is currently expanding exponentially presents a huge potential for Malaysia to make her mark in this industry. In achieving its goal to become a global halal hub by 2020, emphasis should not merely be placed on the production of the halal food products but also on its promotional aspect. Hence, this paper will highlight some preliminary findings on the linguistic feature of the promotional discourse of halal food. The research which was based on a text-linguistic analysis utilised corpus-based techniques to examine the genre of promotional discourse. This preliminary investigation involved an analysis of fifty written materials on halal food which was acquired via various sources. The findings brought to light the words and phrases, discursive structures and visual representations typical in marketing halal food. Most importantly, it provides suggestions in improving the promotional language of halal food. This preliminary study clearly shows the importance of utilising the most appropriate language in conveying the idea of ‘halal’ as prescribed in the Holy Quran especially in gaining the trust of the consumers.